REAL TIME SIMULATION OF NEW DEFENSE SCHEME BASED ON CENTRALIZED REMEDIAL ACTION FOR BATAMBINTAN ELECTRICAL SYSTEM IMPLEMENTATION - Yosia, Nuel
System reliability is the main factor that is maintained in the continuity of the electricity system operation. In the event of a major disruption to the power system, a defense scheme can work quickly and safely to restore the system. Existing defense systems and disruptions that can lead to instability consist of UFLS, OGS, and other schemes. This scheme describes the design of the Centralized Remedial Action Scheme for the existing scheme implemented in the defense scheme in the BatamBintan system. The CRAS scheme will use the HYPERSIM simulator with OPALRT as Hardware In The Loop to perform real-time simulations, the SEL-3530 RTAC as the main processor for the RAS algorithm, and SEL 751 as the mitigation relay IED to send digital output CB commands back to HYPERSIM, where all This security equipment will be connected using an ethernet cable and communicated using the IEC 61850 GOOSE Protocol. The 8 types of vulnerability in the system are implemented as an event-based algorithm that immediately executes through critical component CB status information, which is then effectively mitigated by using load shedding and generation steps. The results obtained are 8 types of vulnerability that can be overcome by minimizing load discharges or generations curtailment by equalizing the power deficit. The system frequency value can stabilize again within 5-8 seconds of the disturbance, and the transient response can return to a stable state value of 50 Hz. CRAS schemes can also be run by equipment with a duration of 30-40 ms from the start of the fault event to the CB opening command.